Hydrogel drug delivery system capable of releasing drugs in time sequence and preparation method of hydrogel drug delivery system
Through the combination of tannin-modified silk fibroprotein hydrogel drug-loading system and drug-loading microspheres, the diversity of anti-inflammatory and osteogenesis needs during tooth extraction healing is solved, and early hemostasis and late osteogenesis effects are achieved , meets the complex needs of the oral microenvironment, improves the effect of wound repair and the biocompatibility and degradability of the materials.
Patent Information
- Application Number
- CN202411378104.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2024-12-27
AI Technical Summary
The requirements for materials at different stages during the healing process of tooth extraction are different. The existing technology is difficult to optimize anti-inflammatory and osteogenic effects, and the oral microenvironment is complex, so the materials need to have wet adhesion and timing drug release capabilities.
Using tannin-modified silk fibroprotein hydrogel drug-loading system, combined with drug-loading microspheres, the first drug is used for anti-inflammatory and the second drug is used to promote osteogenesis, and through specific concentration and volume ratio configurations, the Early hemostasis and late osteogenesis effects, using PLGA or platelet-rich fibrin as microsphere materials to achieve pulsed drug release.
Hemostasis and anti-inflammatory are achieved in the early stages of tooth extraction wound healing, and osteogenesis is promoted in the late stage, meeting the repair needs of different stages, improving the effect of wound repair and the biocompatibility and degradability of the material.
Smart Images

Figure CN119185185A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of drug carrier materials, in particular to a hydrogel drug-carrying system capable of sequential drug release and a preparation method thereof. Background Art
[0002] In oral clinical medicine, tooth extraction wound regeneration generally needs to go through the hemostatic and inflammatory phases, the proliferation phase, and the remodeling phase. Moreover, tooth extraction wound healing needs to withstand the complex changes in the oral microenvironment, and when tooth extraction wounds are regenerated, hemostatic, anti-inflammatory, and osteogenic materials are needed.
[0003] The healing of tooth extraction wounds needs to go through five stages. The first stage is the bleeding and blood clot formation of the tooth extraction wound, which takes about 24 hours after tooth extraction. The second stage is the organization of blood clots and the formation of granulation tissue, which starts 24 hours and is completed in 7 days. The third stage is the replacement of granulation tissue by connective tissue and epithelial tissue, which starts 3-4 days and is completed in about 20 days; during this stage, new bone begins to form 5-8 days after surgery, and immature fibrous bone gradually fills the extraction socket. The fourth stage is the replacement of connective tissue by original fibrous bone. After about 38 days, 2 / 3 of the extraction socket is filled with fibrous bone, and bone tissue is completely formed after 3 months; the fifth stage is the replacement of immature bone by mature bone tissue. Among them, the functional reconstruction of the alveolar process begins 3 days after surgery.
[0004] Based on the above five stages, the requirements for materials in different stages of tooth extraction wound healing are different. Therefore, it is necessary to develop a hydrogel drug delivery system with timed drug release and its preparation method, which can adapt to the needs of different stages of wound repair and optimize the anti-inflammatory and osteogenesis effects. Summary of the invention
[0005] In order to adapt to the needs of different stages of wound repair and optimize the anti-inflammatory and osteogenesis effects, the present invention provides a hydrogel drug delivery system capable of timed drug release and a preparation method thereof.
[0006] The present invention is achieved by adopting the following technical solutions: A hydrogel drug-carrying system capable of timed drug release comprises a hydrogel, a first drug and drug-carrying microspheres; the material of the hydrogel comprises tannic acid-modified silk fibroin; the first drug and the drug-carrying microspheres are dispersed in the hydrogel; the first drug is at least used for anti-inflammatory; the drug-carrying microspheres comprise a second drug and a shell layer surrounding the second drug; and the second drug is at least used for promoting osteogenesis.
[0007] The hydrogel drug-carrying system with timed drug release provided by the present invention can completely seal the wound in the early stage of tooth extraction wound healing to achieve the purpose of hemostasis, perform favorable immunomodulation to resist inflammation, and create a favorable osteogenic microenvironment in the late stage of tooth extraction wound healing. Among them, the hydrogel can meet the requirements of wet viscosity; the first drug can meet the purpose of early anti-inflammatory; loading the second drug into the drug-carrying microspheres can enable the second drug to meet the purpose of late osteogenic.
[0008] Among them, silk fibroin (SF) has the advantages of good biocompatibility, low immunogenicity and predictable degradation. Since the oral wound surface is in a dynamic temperature and humidity environment, it will inevitably be washed by talking, chewing, and saliva, so the hydrogel needs to have good wet adhesion. Modifying silk fibroin with tannic acid (for example, tannic acid and silk fibroin are dynamically cross-linked through hydrogen bonds) to form silk fibroin-tannic acid hydrogel can improve the wet adhesion of the hydrogel, so that the hydrogel has good wet adhesion, loading capacity and sealing performance.
[0009] Furthermore, the material of the shell layer includes polylactic acid-glycolic acid copolymer or chitosan.
[0010] The above materials have good biocompatibility and biodegradability and are suitable as drug delivery materials. Among them, polylactic acid-glycolic acid copolymer (PLGA) is randomly polymerized from two monomers, lactic acid and glycolic acid. The specific PLGA can release drugs in a pulsed manner to achieve a large amount of drug release in the later stage.
[0011] In practical applications, PLGA drug-loaded microspheres can be replaced by platelet-rich fibrin (PRF).
[0012] Further, the first drug includes one or any combination of diclofenac potassium (DP), loxoprofen sodium, aspirin, indomethacin, ibuprofen, ketorolac, meloxicam, celecoxib and flurbiprofen axetil. The concentration of the first drug in the hydrogel drug delivery system is 1 mg / mL to 5 mg / mL, for example, 1 mg / mL, 2 mg / mL, 3 mg / mL, 4 mg / mL, and 5 mg / mL.
[0013] The first drug has the advantages of being injectable, flexible and adjustable, self-healing, biocompatible and biodegradable. When the concentration of the first drug in the hydrogel drug delivery system is 1 mg / mL to 5 mg / mL, the amount of the first drug in the hydrogel drug delivery system can meet the needs of early anti-inflammatory.
[0014] Further, the second drug includes one or any combination of strontium ranelate, teriparatide, abalotriptyline, alendronate sodium, salmon calcitonin, teridinol, ipriflavone and denosumab. The mass proportion of the second drug in the drug-loaded microspheres is 3% to 15%, for example, 3%, 5%, 10%, 15%.
[0015] The second drug is a drug used clinically to treat osteoporosis. In the dental field, it has shown the potential to improve the quality of bone around implants, reduce root resorption during orthodontic tooth movement, and reduce alveolar bone resorption in periodontitis. When the mass proportion of the second drug in the drug-loaded microspheres is 3% to 15%, the amount of the second drug in the hydrogel drug-loaded system can meet the requirements of osteogenesis in the later stage.
[0016] Furthermore, the concentration of the drug-loaded microspheres in the hydrogel drug-loaded system is 0.03 g / mL to 0.09 g / mL, for example, 0.03 g / mL, 0.04 g / mL, 0.05 g / mL, 0.06 g / mL, 0.07 g / mL, 0.08 g / mL, and 0.09 g / mL.
[0017] When the concentration of drug-loaded microspheres in the hydrogel drug delivery system is 0.03 g / mL~0.09 g / mL, firstly, the amount of the second drug in the hydrogel drug delivery system can meet the requirements of osteogenesis in the later stage, and secondly, the content of drug-loaded microspheres in the hydrogel drug delivery system can be within an appropriate range, which is beneficial to the preparation of the hydrogel drug delivery system.
[0018] Furthermore, in the material forming the hydrogel, the volume ratio of tannic acid to silk fibroin ranges from 4:6 to 8:2, for example, 4:6, 5:5, 6:4, 7:3, or 8:2.
[0019] When the volume ratio of tannic acid to silk fibroin is in the range of 4:6~8:2, firstly, the wet adhesion properties of the hydrogel can be further improved; secondly, the gelation rate of the hydrogel can be further improved, thereby improving the feasibility of hydrogel preparation.
[0020] A method for preparing a hydrogel drug-carrying system capable of timed drug release, the method being used to prepare a biological coating with antibacterial effect as described in the present invention, the method comprising: Step S1: forming drug-loaded microspheres.
[0021] Step S2: preparing a first mixed solution, the first mixed solution comprising a first solvent, tannic acid and drug-loaded microspheres; the first solvent is water or phosphate buffer.
[0022] Step S3: preparing a second mixed solution; the second mixed solution includes water, silk fibroin and the first drug.
[0023] Step S4: Mix the first mixed solution and the second mixed solution to obtain a hydrogel drug delivery system.
[0024] The above method has the advantages of simple and feasible process, and can improve the feasibility of preparing the hydrogel drug delivery system.
[0025] Furthermore, in the first mixed solution, the mass fraction of tannic acid is 8% to 12%, for example, 8%, 9%, 10%, 11%, and 12%. In the second mixed solution, the concentration of silk fibroin is 0.008 g / mL to 0.012 g / mL, for example, 0.008 g / mL, 0.009 g / mL, 0.010 g / mL, 0.011 g / mL, and 0.012 g / mL.
[0026] By setting in this way, the contents of tannic acid and silk fibroin in the hydrogel can be within a set range, and the concentration of drug-loaded microspheres in the hydrogel drug-loaded system can be within a set range.
[0027] Further, step S4 includes: mixing the first mixed liquid and the second mixed liquid in a volume ratio of 7:3.
[0028] Further, step S1 includes: Step S1.1: dissolving poly(lactic acid-co-glycolic acid) in an organic solvent to obtain a first solution; Step S1.2: adding water, ammonium bicarbonate and the second drug to the first solution to obtain a third mixed solution; Step S1.3: subjecting the third mixed solution to ultrasonic treatment; Step S1.4: adding the ultrasonicated third mixed solution to the polyvinyl alcohol solution and stirring; Step S1.5: After centrifugation, the supernatant is removed, washed, and freeze-dried to obtain drug-loaded microspheres.
[0029] The above method has the advantages of simple and feasible process, and can improve the feasibility of preparing drug-loaded microspheres.
[0030] The present invention provides a new hydrogel drug delivery system, which can completely seal the wound in the early stage of tooth extraction wound healing to achieve the purpose of hemostasis, perform favorable immunomodulation to fight inflammation, and create a favorable osteogenic microenvironment in the later stage of tooth extraction wound healing. Among them, the hydrogel can meet the requirements of wet viscosity; the first drug can meet the purpose of early anti-inflammatory; loading the second drug into the drug-loaded microspheres can make the second drug meet the purpose of late osteogenesis. The present invention provides a hydrogel drug delivery system that can release drugs in a timed manner, which can be applied to the technical field of drug carrier materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1It is a schematic structural diagram of the hydrogel drug delivery system of the present invention; Figure 2 is a SEM image of the blank hydrogel in Example 3 of the present invention; Figure 3 is a SEM image of the drug-loaded microspheres in Example 4 of the present invention; Figure 4 is a SEM image of the hydrogel drug delivery system in Example 5 of the present invention; Figure 5 is a cumulative release curve diagram of the hydrogel drug delivery system at different time points in Example 5 of the present invention; Figure 6 is a SEM image of the hydrogel drug delivery system after drug release in Example 5 of the present invention; Figure 7 This is a graph showing the results of the ELISA method for the hydrogel drug delivery system in Example 5 of the present invention; Figure 8 is a graph showing the RT-qPCR results of the hydrogel drug delivery system in Example 5 of the present invention; Fig. 9 is a flow cytometry experiment result diagram of the hydrogel drug delivery system in Example 5 of the present invention; Fig.10 is a flow cytometry experiment result diagram of the hydrogel drug delivery system in Example 5 of the present invention; Fig.11 This is a graph showing the results of an in vitro osteogenesis experiment of the hydrogel drug delivery system in Example 5 of the present invention; Fig.12 This is a graph showing the results of an in vitro osteogenesis experiment of the hydrogel drug delivery system in Example 5 of the present invention; Fig.13 It is a cumulative release curve diagram of the comparative hydrogel drug delivery system at different time points in Comparative Example 1 of the present invention.
[0032] In the figure, 1-hydrogel, 2-first drug, 3-drug-loaded microspheres, 31-second drug, 32-shell layer. DETAILED DESCRIPTION Example
[0033] In this embodiment, steps R1 to R3 are used to prepare a silk fibroin (SF) solution.
[0034] Step R1: degumming. Step R1 includes steps R1.1 to R1.6.
[0035] Step R1.1: Prepare 1L (or 3L) of boiling water and pour it into an iron pot (5L capacity), add 2.12g (or 6.36) of anhydrous sodium carbonate, and heat it at 100℃ with a constant temperature magnetic stirrer. Cut the cocoon in half with scissors, weigh 15g of cocoon, put it into 1L of boiling 0.02M sodium carbonate solution, and use a glass rod to properly press the floating cocoon into the boiling solution, soak the cocoon in the solution, and boil it at 100±2℃ for 1h.
[0036] Step R1.2: Use a glass rod to scoop out the boiled silk and transfer it to a beaker. Rinse the silk repeatedly with ultrapure water until the ultrapure water becomes clear and wring out the silk.
[0037] Step R1.3: Prepare 1L (or 3L) of 0.02M sodium carbonate solution again, boil it at 100℃, stretch the wrung-out silk roughly, and put it into the beaker and continue boiling for 1h.
[0038] Step R1.4: Repeat the cleaning process of step R1.2.
[0039] Step R1.5: Repeat the boiling process of step R1.3, and then repeat the cleaning process of step 2.
[0040] Step R1.6: After boiling the silk three times and squeezing out the moisture, spread it on the tin foil as much as possible and dry it at a constant temperature of 40°C overnight to complete the degumming process.
[0041] Step R2: prepare a 9.3 M LiBr solution. Step R2 includes steps R2.1 to R2.3.
[0042] Step R2.1: Prepare 50mL (80ml-20g degummed silk; or 100ml-25g) 9.3M LiBr solution: prepare and use immediately, weigh 40.3852g LiBr, pour into a beaker, add about 35ml ultrapure water and stir with a glass rod to dissolve it; the volume can be determined by mass, which is about 160ml lithium bromide = 130g lithium bromide solid + 120g pure water.
[0043] Step R2.2: Transfer the dissolved solution to a 50 ml volumetric flask, rinse the beaker with ultrapure water, and dilute to the mark. Since the solution is in a state of thermal expansion at the initial stage, wait for the solution in the volumetric flask to cool to room temperature and then dilute to the mark again with ultrapure water.
[0044] Step R2.3: When used, pour the LiBr solution in the volumetric flask into a clean 50 ml centrifuge tube for easy access.
[0045] Step R3: Dissolving the silk. Step R3 includes steps R3.1 and R3.2.
[0046] Step R3.1: Heat lithium bromide in a 60℃ water bath, change into clean gloves, weigh 12.5g of dry degummed silk, take a fist-sized portion of silk and put it into a beaker containing lithium bromide, press with a glass rod to fully immerse the silk, and add the next portion after it is completely dissolved and no fibers can be seen.
[0047] Step R3.2: Seal the glass beaker with plastic wrap, put it in a 60±5℃ water bath, and react at constant temperature for 4 hours to obtain a brown-yellow transparent solution.
[0048] Step R4: dialysis. Step R4 includes steps R4.1 to R4.5.
[0049] Step R4.1: First, clamp one side of the dialysis bag with a clamp and transfer the transparent solution after dissolving the silk into the dialysis bag. Then, rinse the glass beaker with a small amount of ultrapure water and pour it into the dialysis bag (3 times), and try to remove the bubbles in the dialysis bag. Then, seal the other end of the dialysis bag with a clamp, and put the dialysis bag with both ends sealed into a beaker filled with 5000ml ultrapure water for dialysis. The first water change time is 1h, the second 4h, and except for overnight, the time interval between each dialysis is 4h, and the water is changed 10 times.
[0050] Step R4.2: Prepare two 2000 ml portions of 10% PEG solution.
[0051] Step R4.3: After dialysis, transfer the dialysis tape into the PEG solution for reverse dialysis experiment for 16 h (or 36 h) without changing the solution.
[0052] Step R4.4: First, take out the dialysis bag, rinse the dialysis tape twice with ultrapure water, then rinse the clamp with ultrapure water (to prevent the PEG solution from being contained in the gap of the clamp), and pour it into a 15ml clean centrifuge tube. Then, put the centrifuge tube into a centrifuge, centrifuge at 10000 r / min for 15 min, gently remove the supernatant with a pipette, and refrigerate at 4℃ for later use.
[0053] Step R4.5: Determine the concentration: Take 200 µL of silk fibroin solution and put it into a weighed clean centrifuge tube, weigh the total weight, then dry it at 37°C for 4 hours, weigh it, and calculate the concentration of the silk fibroin solution. Example
[0054] In this embodiment, tannic acid (TA) solution is prepared by using steps M1 and M2.
[0055] Step M1: Prepare PBS buffer with pH=3.5. Specifically, first calibrate the pH meter with a standard pH buffer reagent; then prepare 100 ml of 0.5M potassium dihydrogen phosphate solution, adjust the pH of the potassium dihydrogen phosphate solution to 3.5 with a dilute phosphoric acid solution with a volume ratio of 1:1, and store the prepared PBS solution in a refrigerator at 4°C.
[0056] Step M2: Preparation of tannic acid (TA) solution. Specifically, first prepare a TA solution with a mass fraction of 10% by weight: weigh 0.5 g of tannic acid and put it into the bottom of a 15 ml clean centrifuge tube, add 4.5 g of PBS solution; then tighten the centrifuge tube and place it on a vortex mixer to fully dissolve it to obtain a yellow transparent liquid. Example
[0057] In this embodiment, blank hydrogel TS was prepared. The specific process includes: weighing the corresponding silk protein solution and tannic acid solution according to different mass ratios, mixing them in a clean centrifuge tube, and gently stirring to obtain the corresponding adhesive product (i.e., blank hydrogel TS). The adhesive product can be stored in a refrigerator at 4°C, and can be taken out when used. It will swell and soften when soaked in an appropriate amount of ultrapure water. .
[0058] In order to confirm the preparation results of the blank hydrogel in this example, a scanning electron microscope (SEM) test was performed, and the results are as follows: Figure 2 As shown. Figure 2 It can be seen that the blank hydrogel has a porous structure and can be used to carry the first drug and drug-loaded microspheres. Example
[0059] In this embodiment, drug-loaded microspheres were prepared using steps N1 to N5.
[0060] Step N1: Dissolve 0.25 g PLGA in 4 mL chloroform and stir for 1-2 h until completely dissolved.
[0061] Step N2: Add 1 mL of ultrapure water and 0.1 g of ammonium bicarbonate (NH 4 HCO 3 ) and 0.0134 g of the second drug, strontium ranelate, followed by ultrasound for 15 minutes.
[0062] Step N3: The solution obtained in step N2 was added to 200 mL of PVA solution, sonicated for 1 min, and stirred for 4 h.
[0063] Step N4: Centrifuge at 1000 rpm for 20 min and remove the supernatant.
[0064] Step N5: washing and freeze-drying.
[0065] In order to confirm the preparation results of the drug-loaded microspheres in this example, SEM tests were performed, and the results are as follows: Figure 3 As shown. Figure 3 It can be seen that the drug-loaded microspheres have a spherical structure and a particle size of about 16.43 μm. Example
[0066] In this embodiment, steps H1 to H3 are used to prepare a hydrogel drug delivery system capable of timed drug release.
[0067] Step H1: Diclofenac potassium was added to the 10 wt % silk fibroin (SF) solution prepared in Example 1 (i.e., the supernatant obtained in step R4.4) to make the concentration of diclofenac potassium 10 mg / mL, to obtain a second mixed solution.
[0068] Step H2: Take three portions of tannic acid (TA) solution prepared in Example 2, add the drug-loaded microspheres (PLGA-Sr) with a drug loading of 5% prepared in Example 4, respectively, so that the mass proportions of the drug-loaded microspheres in the hydrogel drug-loaded system are 3%, 6%, and 9%, respectively, and the concentrations are 0.03 g / mL, 0.06 g / mL, and 0.09 g / mL, to obtain the first mixed solution A, the first mixed solution B, and the first mixed solution C. Among them, the mass fractions of tannic acid in the first mixed solution A, the first mixed solution B, and the first mixed solution C are all 10%.
[0069] Step H3: At room temperature, the second mixed liquid obtained in step H1 and the first mixed liquid A obtained in step H2 are mixed in a volume ratio of 3:7 to obtain a hydrogel drug delivery system A; the second mixed liquid obtained in step H1 and the first mixed liquid B obtained in step H2 are mixed in a volume ratio of 3:7 to obtain a hydrogel drug delivery system B; the second mixed liquid obtained in step H1 and the first mixed liquid C obtained in step H2 are mixed in a volume ratio of 3:7 to obtain a hydrogel drug delivery system C.
[0070] In order to confirm the preparation results of the hydrogel drug delivery system B of this example, SEM test was carried out, and the results are as follows: Figure 4 As shown. Figure 4 It can be seen that the drug-loaded microspheres can be dispersed in the hydrogel and fill part of the pores of the hydrogel.
[0071] Step H4: K-treating the hydrogel drug delivery system A, hydrogel drug delivery system B, and hydrogel drug delivery system C obtained in step H3 respectively. + With Sr 2+ The drug release test obtained at different time points showed that the cumulative release curves were Figure 5 shown.
[0072] Depend on Figure 5It can be seen that compared with hydrogel drug delivery system A (the mass proportion of drug-loaded microspheres in the hydrogel drug delivery system is 3%) and hydrogel drug delivery system C (the mass proportion of drug-loaded microspheres in the hydrogel drug delivery system is 9%), hydrogel drug delivery system B (the mass proportion of drug-loaded microspheres in the hydrogel drug delivery system is 6%) can achieve the highest release amount under fully controlled costs. Among them, the K of hydrogel drug delivery system B is + The burst release was achieved within 2 days, indicating that it is expected to control inflammation at an early stage. 2+ The accelerated release after 3 days initiated the bone repair process, indicating that it is expected to continue to promote bone repair after controlling inflammation, proving that the hydrogel drug delivery system provided in this application has a timed release characteristic.
[0073] In addition, this embodiment also carried out the following tests and characterizations on the hydrogel drug delivery system.
[0074] Test 1: SEM test was performed on the sample of hydrogel drug delivery system B after the drug release test in step H4. The results are as follows: Figure 6 As shown. Figure 6 It can be seen that the first drug, diclofenac potassium, and the second drug, strontium ranelate, can both be successfully released.
[0075] Test 2: Anti-inflammatory experiment was performed on the hydrogel drug delivery system B obtained in step H3. Anti-inflammatory experiment was performed on mouse mononuclear macrophage leukemia cells (Raw 264.7, ATCC). Hydrogel TS was prepared with 3.5 mL TA solution (10%) and 1.5 mL SF solution (see Example 3 for its preparation method). Hydrogel TSDS was prepared with 3.5 mL TA solution (10%) containing 15 mg strontium ranelate and 1.5 mL SF solution containing 15 mg diclofenac potassium (see Comparative Example 1 for its preparation method). TS, TSDS, and hydrogel drug delivery system B (abbreviated as TSD-NP@S in the figure) were respectively soaked in 50 mL high-glucose DMEM culture medium containing 10% FBS and 1% penicillin-streptomycin (hereinafter referred to as blank culture medium 1) for 24 hours, extracted and filtered with a bacterial filter to obtain the corresponding extract culture medium. 2*10 were inoculated in each well of a 6-well plate. 5 Raw 264.7 macrophages were cultured in blank medium 1 for 24 hours. Then, 1 mL of the corresponding extract medium and 1 mL of lipopolysaccharide (LPS) solution (20 μg / mL, dissolved in blank medium 1) were added to each well. The blank group (abbreviated as Blank in the figure) only added 2 mL of blank medium 1, and the LPS group added 2 mL of LPS solution (10 μg / mL, dissolved in blank medium 1). After all groups were cultured for 4 hours, all groups were replaced with the corresponding blank medium 1 / extract medium for 24 hours.
[0076] (1) The cell supernatant after 24 hours of culture was used for enzyme-linked immunosorbent assay (hereinafter referred to as ELISA) and the extracted RNA was used for reverse transcription real-time quantitative fluorescence quantitative PCR (RT-qPCR) testing. The ELISA test results are as follows: Figure 7 As shown, the RT-qPCR test results are as follows Figure 8 As shown. Among them, Figure 7 and Figure 8 In the figure, Blank represents the blank group, LPS represents LPS, TS represents the TS group, TSDS represents the TSDS group, and TSD-NP@S represents the hydrogel drug delivery system B. Figure 7 (a) It can be seen that the positive expression of TNF-α (M1 type index) in the hydrogel drug delivery system B group was significantly reduced compared with the LPS inflammatory stimulation group, proving that the hydrogel drug delivery system B can resist M1 polarization. Figure 7 (b) It can be seen that Arg (M2 type indicator) in hydrogel drug delivery system B was significantly higher than that in other groups, proving that the hydrogel drug delivery system can promote M2 polarization and has good anti-inflammatory properties. Figure 8 In the above example, inos and cd80 are M1 indicators, and Arg is M2 indicator. Figure 8 It can be seen that the hydrogel drug delivery system can resist M1 polarization, promote M2 polarization, and has good anti-inflammatory properties.
[0077] (2) After 24 hours of culture, RAW 264.7 cells were blown off and collected for flow cytometry testing. The results are as follows: Fig. 9 and Fig.10 As shown. Fig. 9 and Fig.10 It can be seen that the hydrogel drug delivery system can resist M1 polarization and has good anti-inflammatory properties. Fig. 9 and Fig.10 For the meanings of Blank, LPS, TS, TSDS, and TSD-NP@S, please refer to the above part.
[0078] Test 3: Osteogenesis experiment was performed on the hydrogel drug delivery system B obtained in step H3. Osteogenesis experiment was performed on mouse embryonic preosteoblasts (MC3T3-E1). Hydrogel TS was prepared with 3.5 mL TA solution (10%) and 1.5 mL SF solution. Hydrogel TSDS was prepared with 3.5 mL TA solution (10%) containing 15 mg strontium ranelate and 1.5 mL SF solution containing 15 mg diclofenac potassium. Hydrogel drug delivery system B was immersed in PBS at 37 degrees Celsius for 3 days to prepare TSD-NP@S* (in order to test the effect of the hydrogel drug delivery system B after the sequential release). TS, TSDS, TSD-NP@S*, and hydrogel drug delivery system B (abbreviated as TSD-NP@S in the figure) were immersed in 5 mL of MEM medium containing 10% FBS and 1% penicillin-streptomycin (hereinafter referred to as blank medium 2) for 24 hours, and then extracted and filtered with a bacterial filter to obtain the corresponding extract medium. 2*10 5 MC3T3-E1 cells were cultured in blank medium 2 for 24 hours. Then, 1.8 mL of osteogenic medium and 0.2 mL of the corresponding extract medium were added to each well and cultured for 7 days. The blank group (control group in the chart) was added with 2 mL of osteogenic medium and cultured for 7 days. The medium was changed once every 2 days. The collected cell supernatant was tested by ELISA; MC3T3-E1 was fixed and stained for alkaline phosphatase. Fig.11 and Fig.12 In the figure, Control represents the blank group, TS represents the TS group, TSDS represents the TSDS group, TSD-NP@S represents the hydrogel drug delivery system B, TSD-NP@S* represents the hydrogel drug delivery system B after the start of sequential release, OCN represents osteocalcin, and OPN represents osteopontin. Fig.11 As shown in Figure 2, compared with the other groups, the positive rate of hydrogel drug delivery system B (TSD-NP@S*) after the start of sequential release was significantly increased. The alkaline phosphatase test results are shown in Figure 2. Fig.12 As shown, the positive rate of hydrogel drug delivery system B was significantly higher than that of other groups. Fig.11 and Fig.12 It can be seen that the in vitro osteogenic alkaline phosphatase results showed that TSD-NP@S had a good osteogenic effect in the early stage, proving that the hydrogel drug delivery system has a good osteogenic effect.
[0079] Comparative Example 1 In this comparative example, a comparative hydrogel drug delivery system TSDS without drug-loaded microspheres was prepared. The preparation steps of the comparative hydrogel drug delivery system were similar to those of Example 5, except that: in step H2, a second drug strontium ranelate equal in amount to the strontium ranelate in the drug-loaded microspheres was added.
[0080] The hydrogel drug delivery system B obtained in step H3 of Example 5 and the comparative hydrogel drug delivery system TSDS obtained in step H3 of Comparative Example 1 were subjected to K + With Sr 2+ The drug release test obtained at different time points showed that the cumulative release curves were Fig.13 shown.
[0081] Depend on Fig.13 It can be seen that compared with the hydrogel drug delivery system B (the mass proportion of drug-loaded microspheres in the hydrogel drug delivery system is 6%), the hydrogel drug delivery system has a higher content of metal ions Sr 2+ Simultaneous release makes the system more compact, affecting drug release.
[0082] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.
Claims
1. A hydrogel drug delivery system capable of timed drug release, characterized in that: The invention comprises a hydrogel (1), a first drug (2) and drug-loaded microspheres (3); the material of the hydrogel (1) comprises tannic acid-modified silk fibroin; the first drug (2) and the drug-loaded microspheres (3) are dispersed in the hydrogel (1); the first drug (2) is at least used for anti-inflammatory effects; the drug-loaded microspheres (3) comprise a second drug (31) and a shell layer (32) surrounding the second drug (31); and the second drug (31) is at least used for promoting osteogenesis.
2. The hydrogel drug delivery system capable of timed drug release according to claim 1, characterized in that: The material of the shell layer (32) includes polylactic acid-glycolic acid copolymer or chitosan.
3. The hydrogel drug delivery system capable of timed drug release according to claim 1, characterized in that: The first drug (2) comprises one or a combination of any two or more of diclofenac potassium, loxoprofen sodium, aspirin, indomethacin, ibuprofen, ketorolac, meloxicam, celecoxib and flurbiprofen axetil; the concentration of the first drug (2) in the hydrogel drug delivery system is 1 mg / mL to 5 mg / mL.
4. The hydrogel drug delivery system capable of timed drug release according to claim 1, characterized in that: The second drug (31) includes one or a combination of any two or more of strontium ranelate, teriparatide, abalotriptyline, alendronate sodium, salmon calcitonin, teridine, ipriflavone and denosumab; the mass proportion of the second drug (31) in the drug-loaded microspheres is 3% to 15%.
5. The hydrogel drug delivery system capable of timed drug release according to claim 1, characterized in that: The concentration of drug-loaded microspheres (3) in the hydrogel drug-loaded system is 0.03 g / mL to 0.09 g / mL.
6. The hydrogel drug delivery system capable of timed drug release according to claim 1, characterized in that: In the material forming the hydrogel (1), the volume ratio of tannic acid to silk fibroin ranges from 4:6 to 8:
2.
7. A method for preparing a hydrogel drug delivery system capable of timed drug release, characterized in that: The method is used to prepare a hydrogel drug delivery system capable of timed drug release according to any one of claims 1 to 7, and the method comprises: Step S1: forming drug-loaded microspheres (3); Step S2: preparing a first mixed solution, the first mixed solution comprising a first solvent, tannic acid and drug-loaded microspheres; the first solvent is water or phosphate buffer; Step S3: preparing a second mixed solution; the second mixed solution includes water, silk fibroin and the first drug (2); Step S4: Mix the first mixed solution and the second mixed solution to obtain a hydrogel drug delivery system.
8. The method for preparing a hydrogel drug delivery system capable of timed drug release according to claim 7, characterized in that: In the first mixed solution, the mass fraction of tannic acid is 8% to 12%; In the second mixed solution, the concentration of silk fibroin is 0.008 g / mL to 0.012 g / mL.
9. The method for preparing a hydrogel drug delivery system capable of timed drug release according to claim 8, characterized in that: Step S4 includes: mixing the first mixed liquid and the second mixed liquid in a volume ratio of 7:
3.
10. The method for preparing a hydrogel drug delivery system capable of timed drug release according to claim 7, characterized in that: Step S1 includes: Step S1.1: dissolving poly(lactic acid-co-glycolic acid) in an organic solvent to obtain a first solution; Step S1.2: adding water, ammonium bicarbonate and the second drug (31) to the first solution to obtain a third mixed solution; Step S1.3: subjecting the third mixed solution to ultrasonic treatment; Step S1.4: adding the ultrasonicated third mixed solution to the polyvinyl alcohol solution and stirring; Step S1.5: After centrifugation, remove the supernatant, wash, and freeze-dry to obtain drug-loaded microspheres (3).
Citation Information
Patent Citations
Composite material as well as preparation method and application thereof
CN112006918A
Sequential-release double-drug-loading hydrogel as well as preparation method and application thereof
CN114652897A
Silk fibroin hemostatic gel as well as preparation method and application thereof
CN115645597A
Drug-loaded nano-composite hydrogel, preparation method thereof and application of drug-loaded nano-composite hydrogel in preparation of drugs for periodontal disease photodynamic therapy
CN116421546A
Hemostatic bone repair hydrogel as well as preparation method and application thereof
CN117883634A
Cited By
Hydrogel microsphere system for sequential delivery of drugs as well as preparation method and application of hydrogel microsphere system
CN120550184A
Hydrogel complex as well as preparation method and application thereof
CN120661731A
